Recent advances in gold nanoparticles for biomedical applications: from hybrid structures to multi-functionality. Issue 22 (22nd May 2019) - Jeong, Hyeon-Ho; Choi, Eunjin; Ellis, Elizabeth; Lee, Tung-Chun
Abstract : Hybrid gold nanoparticles for biomedical applications are reviewed in the context of a novel classification framework and illustrated by recent examples. Abstract : Gold nanoparticles (Au NPs) are arguably the most versatile nanomaterials reported to date. Recent advances in nanofabrication and chemical synthesis have expanded the scope of Au NPs from classical homogeneous nanospheres to a wide range of hybrid nanostructures with programmable size, shape and composition. Novel physiochemical properties can be achieved via design and engineering of the hybrid nanostructures. In this review we discuss the recent progress in the development of complex hybrid Au NPs and propose a classification framework based on three fundamental structural dimensions (length scale, complexity and symmetry) to aid categorising, comparing and designing various types of Au NPs. Their novel functions and potential for biomedical applications will also be discussed, featuring point-of-care diagnostics by advanced optical spectroscopy and assays, as well as minimally invasive surgeries and targeted drug delivery using multifunctional nano-robots.